Cafe as a Representation of the Lifestyle of the Urban Community - Ahmad, Harun; Sumarti, Endang; Sriwulandari, Yunita Anas (Technium Social Sciences Journal, 2022)
Café is one of the contemporary products that has become an arena of lifestyle battles. Supported by a culture of consumerism and commodity fetishism, the Café then transformed into a lifestyle representation of urban society. There are many phenomena that support this thesis. Those who come to the Café are not only to fulfill their basic needs (the need to drink coffee), but more than that, which is to show others their existence with all the success they have achieved. Drinking coffee in a café with the aim of imaging is the core of the culture of consumerism and commodity fetishism, which Anthony Giddens (1991:198) calls a human identity project.